Comparative Analysis of ADDIE and ASSURE Models in Designing Learning Media Applications - Hasna Nirfya Rahmandhani; Ema Utami (Jurnal Educative: Journal of Educational Studies, 2022)
Learning media is an important part of producing quality learning. Therefore, learning media development is needed that supports the learning objectives. Several models can be used in designing learning media, such as the ADDIE and ASSURE models. The ADDIE model has the following development steps: (1) Analysis, (2) Design, (3) Development, (4) Implementation, and (5) Evaluation. While the ASSURE model has the following development steps: (1) Analyzing learners, (2) Stating learning objectives, (3) Selecting media and methods, (4) Utilizing media and methods, (5) Requiring learner response, (6) Evaluating. The purpose of this study is to compare the use of the ADDIE model and ASSURE model according to the learning objectives. The research was conducted using the literature review method from 36 articles and books that discuss the making of learning media with ADDIE and ASSURE design models. The literature review references were taken from Google Scholar with publication years between 2012 - 2022. The results of this study show that the use of the ADDIE design model is more effective in designing learning media applications because it focuses on material content and application feasibility so that students can use it optimally to achieve goals. Meanwhile, the ASSURE model is more effective for designing learning systems or teaching materials because itfocuses on the application of learning media design models that can attract student interest to generate learning motivation.